Distributed leadership and conflict management in secondary level teachers: network 4-ugel 01, 2017 - Galindo Quispe, Ana Isabel (2021)
The present research work entitled: "Distributed Leadership and Conflict Management in Secondary Level Teachers: Network 04 - UGEL 01", was carried out with the objective of determining the relationship that exists between the variables: Distributed Leadership and Conflict Management in The teachers of the Secondary Level: Network 04 - UGEL 01, the study arises within the framework of school management commitments and the improvement of teaching performance.  It is a correlational descriptive type of research because it establishes a direct relationship between the variables: Distributed Leadership and Conflict Management. The population was constituted by 122 teachers of Secondary Level comprising the educational institutions of Network 4, in this sense the study was census where all the research units are considered as sample to those who were administered two instruments that were validated by trial of experts and determined with high reliability: distributed leadership questionnaire - LDAG (cronbach alpha = 0.836) and the conflict management questionnaire - GCAG (cronbach alpha = 0.901). It was concluded that there is a direct and significant relationship between the distributed Leadership and the management of conflicts of the teachers of the educational institutions of the Network 04 of the UGEL 01 in the year 2017, with a Spearman correlation coefficient of 0.606 and a value p = 0,000 lower than the 0.05 level, the alternative hypothesis is accepted and the null hypothesis is rejected, confirming the relationship between the variables analyzed in this research paper.